MANAJEMEN SEKOLAH BERASRAMA DALAM MENINGKATKAN PRESTASI AKADEMIK SISWA MTS HIDAYATUL MULIMIN 1 KUBU RAYA - Ferianto Ferianto; U. Husna Asmara; Sukmawati Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractBoarding Education Management in improving student academic achievement at MTs Hidayatul Muslimin 1 Kubu Raya is an education with a boarding system, a program that is very supportive of improving student academic achievement, all student activities can be directed and controlled by the hostel manager in achieving an educational goal set by the hostel. . The purpose of this research is to obtain descriptive information with a qualitative approach, using the type of case study research. The preparation of this writing uses primary and secondary data through interviews, observation and documentation. Data analysis using data reduction, data presentation, and drawing conclusions. Researchers found that boarding school management includes:Good planning, madrasahs involve every element of the madrasah in a plan.Organizing boarding schools begins with a mapping of education and education staff, recruitment of employees, division and delegation of tasks and authorities. The implementation of boarding schools is very good, this is because the elements of the madrasah are responsible for the assigned tasks. Boarding school supervision must be a concern, so that supervision can be optimal, and supporting instruments in supervision are needed, so that supervision can be properly directed and the objectives of supervision can be achieved. Keywords: Management, Boarding School, Achievement